Towards Improved Characterisation and Synthesis of Two-Dimensional Transition Metal Dichalcogenides - Cullen, Conor Patrick (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2021)
Two-dimensional (2D) transition metal dichalcogenides (TMDs) are a fast growing and highly researched area in modern materials science. The numerous potential advances, made possible by their oft-quoted, varied, and layer-dependent properties, has led to a proportionate gold rush across the periodic table for suitable materials to be synthesised on the nanoscale. A consequence of the gold rush haste is that occasionally the due diligence in terms of accurate and refined characterisation of the TMD material itself is overlooked in order to focus on more forward-looking aspects such as fabrication of electrical or electrochemical applications. This has resulted in a lack of coherency within literature, particularly between fundamental property studies which may utilise completely pristine material with few defects and no contamination or oxides present. As well as studies which are application oriented such as device fabrication or electrochemical applications. For both of these examples the TMD material is likely to be partially degraded or contaminated by some processing steps or by chemical reactions. XPS and Raman spectroscopy can both be utilised to great effect to characterise the state of a TMD material or to measure any changes or products during an experiment. This is widely known and both techniques are prevalent in 2D TMD literature, unfortunately however, the resultant data are not always appropriately analysed or well-presented from these techniques. XPS in particular is considered to be frequently incorrectly analysed in this field. Accordingly, to improve such problematic elements of the literature, this thesis entitled Towards Improved Synthesis, Characterisation, and Analysis of Two-Dimensional Transition Metal Dichalcogenides considered a characterisation prioritised examination of the synthesis, chemical reactivity, and stability of several 2D TMD materials in order to broaden the knowledge of their analysis. Particular focus was paid to XPS, with the intention of constructing a transparent understanding of the analysis of TMD XPS spectra. This was achieved by thorough examination of the TMDs in multiple chemical environments. The first study entailed the synthesis of the prototypical TMD, MoS2. High-quality, largely monolayer crystals of MoS2 were successfully synthesised on SiO2 using a chemical vapour deposition (CVD) method. These MoS2 crystals with sides up to ~100µm in length, displayed the prominent photoluminescence (PL) and Raman spectra characteristic of monolayer MoS2. Metrics were established to monitor the crystalline quality of the MoS2 using these spectra. The effects of NH3 plasma on this CVD MoS2 were studied to examine the chemical reactivity of MoS2. XPS analysis established that NH3 plasma treatment resulted in the controllable substitutional doping of nitrogen atoms into the MoS2 lattice with removal of sulfur atoms. The analysis of this served to clarify the XPS features attributed to nitrogen doping of MoS2, these components have been frequently confused in the literature. Beyond this, the effects of NH3 plasma treatment were found to have a pronounced impact on the MoS2. The monolayer MoS2 PL shifted to higher energy in a tuneable and stable manner. With maximum shifts to over 2 eV (620 nm). The structural impact of this process was also examined, Raman analysis determined that NH3 plasma was a highly surface sensitive process with plasma-treated monolayers of MoS2 losing the characteristic Raman modes while bilayers of MoS2 were found to transition to monolayer-like Raman signal after plasma treatment, indicating that the top-most layer was predominantly affected. Low-frequency Raman spectroscopy was used to confirm this decoupling of the bilayer stack of MoS2. By increasing the duration of the plasma exposure it was discovered that the increasing strain in the crystal resulted in nanoscroll formation as the individual crystals rolled up. A detailed XPS analysis of ten transition metal chalcogenides was performed. Including sulfides, selenides, and tellurides of Mo, W, and Pt, these encompass the bulk of materials studied in modern TMD literature. The materials were synthesised as large-area uniform thin-films using a direct chalcogenisation of pre-deposited metal films method called thermally assisted conversion (TAC). The XPS spectra of these materials were analysed with curve-fitting to identify the individual components of each core-level spectrum. Each fitted spectrum was discussed in detail and considered alongside the corresponding Raman spectra for each material, these complementary characterisation methods provide a considerably more accurate understanding of the state of the material. To establish a wide library of consistent characterisation data, each of these ten materials were also annealed in ambient at several temperatures up to 400 °C. This forced degradation of the materials allowed their relative stabilities to be indicated as well as generating their most common oxides and other degradation products. Comprehensive analysis of these annealed materials expands the assembled library of data here substantially and increases its utility particularly for comparison to applications focused research where TMD degradation is common. Finally, the utility of these developed synthesis and characterisation methods are exemplified with the study of the two closely linked platinum sulfide materials. Aspects of PtS2 and PtS are frequently confused in literature due to their uncommon coexistence and limited literature data. XPS and Raman analysis were utilised here to unambiguously distinguished the two materials. This enabled optimisation of efficient methods to synthesise high-purity polycrystalline thin films of both the non-layered PtS and the layered PtS2 using TAC methods. In summary, this thesis prioritises the reliable characterisation of the materials, synthesis methods to produce a variety of 2D TMD materials were demonstrated including for high-quality monolayer MoS2. Comprehensive XPS and Raman characterisations were carried out on 10 TMD materials to assemble an array of complementary characterisation data for the TMD materials across multiple chemical environments.
APPROVED
Keywords: 2D Materials; X-ray photoelectron spectroscopy (XPS); Transition Metal Dichalcogenides (TMDs); MoS2; MoSe2; Chemical vapour deposition (CVD); MoTe2; WS2; WSe2; WTe2; PtS; PtS2; PtSe2; PtTe2